Comparative Study on Physicochemical and Biological Parameters of Water among Fish Culture and Reconstructed Pond at Jahangirnagar University Campus, Bangladesh (Journal of Environmental Science and Natural Resources, 2016)
The study was conducted to investigate the physicochemical and biological parameters of fish culture and reconstructed pond at Jahangirnagar university campus. The physicochemical parameters of water in culture and reconstructed pond were analyzed during February to September, 2014 and the mean value of temperature were 30.21±0.89 ºC and 29.96±0.91 ºC, pH value were 7.20±0.29 and 6.97±0.39, Dissolve Oxygen (DO) value were 6.44±0.40mg-1 and 6.22±0.30mg-1, Biochemical Oxygen Demand (BOD5) value were 1.02±0.32mg-1 and 0.78±0.18mg-1, Total Dissolve Solid (TDS) were 0.69±0.04mg-1 and 0.64±0.04mg-1, Electric Conductivity (EC) value were 215.38±21.27?Scm-1 and 128.58±1.10?Scm-1. From the study of biological parameter, it was found that Chlorophyceae and Euglenophyceae were dominant in studied ponds and the abundance of phytoplankton are in the order of Chlorophyceae >Euglenophyceae > Bacillariophyceae > Cyanophyceae. The highest productivity was found in culture pond which indicates the suitability of using for aquaculture.J. Environ. Sci. & Natural Resources, 9(1): 1-7 2016